Translation of SOX10 3' untranslated region causes a complex severe neurocristopathy by generation of a deleterious functional domain. - Wegner, Michael; et al. (Human Molecular Genetics, 2007)
Peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome and Hirschsprung disease (PCWH) is a complex neurocristopathy caused by SOX10 mutations. Most PCWH - associated SOX10 mutations result in premature termination codons (PTCs), for which the molecular mechanism has recently been delineated. However, the first mutation reported to cause PCWH was a disruption of the native stop codon that by conceptual translation extends the protein into the 3′ untranslated region (3′-UTR) for an additional 82 residues. In this study, we sought to determine the currently unknown molecular pathology for the SOX10 extension mutation using in vitro functional assays. Despite the wild-type SOX10 coding sequence remaining intact, the extension mutation led to severely diminished transcription and DNA-binding activities. Nevertheless, it showed no dominant-negative interference with wild-type SOX10 in vitro. Within the 82-amino acid tail, an 11-amino acid region (termed the WR domain) was responsible primarily for the deleterious properties of the extension. The WR domain, presumably forming an α-helix structure, inhibited SOX10 transcription activities if inserted in the carboxyl-terminal half of the protein. The WR domain can also affect other transcription factors with a graded effect when fused to the carboxyl termini, suggesting that it probably elicits a toxic functional activity. Together, molecular pathology for the SOX10 extension mutation is distinct from that of more common PTC mutations. Failure to properly terminate SOX10 translation causes the generation of a deleterious functional domain that occurs because of translation of the normal 3′-UTR; the mutant fusion protein causes a severe neurological disease. © The Author 2007. Published by Oxford University Press. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2007.med.IB.LPCIPDBI.transl